2015
DOI: 10.1088/0253-6102/64/1/103
|View full text |Cite
|
Sign up to set email alerts
|

Density Transition Based Self-Focusing of cosh-Gaussian Laser Beam in Plasma with Linear Absorption*

Abstract: Density transition based self-focusing of cosh-Gaussian laser beam in plasma with linear absorption has been studied. The field distribution in the plasma is expressed in terms of beam width parameter, decentered parameter, and linear absorption coefficient. The differential equation for the beam width parameter is solved by following Wentzel–Kramers–Brillouin (WKB) and paraxial approximation through parabolic wave equation approach. The behaviour of beam width parameter with dimensionless distance of propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Ponderomotive [45], thermal [46], and relativistic [47] mechanisms can individually lead to the SF of an intense laser beam in plasma. Nonlinear propagation of a laser beam in unbounded plasma, taking into account the SF phenomenon during its propagation, has been theoretically investigated in many articles (see [32,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] to give just a few examples).…”
Section: Introductionmentioning
confidence: 99%
“…Ponderomotive [45], thermal [46], and relativistic [47] mechanisms can individually lead to the SF of an intense laser beam in plasma. Nonlinear propagation of a laser beam in unbounded plasma, taking into account the SF phenomenon during its propagation, has been theoretically investigated in many articles (see [32,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] to give just a few examples).…”
Section: Introductionmentioning
confidence: 99%
“…Influence of density transition on self-focusing of laser in plasma was studied [15] and it was concluded that an earlier and efficient self-focusing of the laser can be observed with density transition whereas due to linear absorption weaker self-focusing occurs in plasma. A remarkable influence of the intensity and decentered parameters on selffocusing of Hermite-cosine-Gaussian laser beam with collisionless plasma was observed.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Also, it has been observed that, under the influence of magnetic field and plasma density ramp, the selffocusing becomes stronger up to great extent. [17] Kant and Wani, [18] examined the behavior of the beam width parameter for normalized distance of propagation at optimized values of decentered parameters, plasma density and various absorption levels. Further, in quantum plasma self-focusing of cosh-Gaussian laser beam was presented by Habibi and Ghamari [19] by following higher order paraxial theory.…”
Section: Introductionmentioning
confidence: 99%